UPAYA PENINGKATAN MEDA ODGJ (MEDICATION ADHERENCE ORANG DENGAN GANGGUAN JIWA) BERBASIS APLIKASI SMARTPHONE - Hartanto, Fajar Agung Dwi; Widyastuti, Novi; Nasriyah, Chotijatun; Cahayani, Dian Ameilia; Anggraini, Cristine (Jurnal Abdi Insani, 2024)
People with mental disorders (ODGJ) who are accompanied by their own families either at home or as outpatients need support to improve medication adherence during their rehabilitation. One of the things that can hinder efforts to improve medication adherence in ODGJ patients (MEDA ODGJ) is non-compliance in taking medication. Based on data from the Yogyakarta City Health Office, the Integrated Service Unit (UPT) of the Tegalrejo Health Center was recorded as having the highest number of visits for patients with mental disorders compared to other health centers. The purpose of this community service activity is to improve medication adherence in ODGJ patients through a smartphone application-based program. The method in this community service activity begins with a Focus Group Discussion (FGD) with health cadres, distribution of initial questionnaires (pre-test), initial socialization about mental disorders and how to handle them, counseling and training in using the application, monitoring and evaluation through distribution of the final questionnaire (post-test) to determine the level of success. The targets of this community service are members of health cadres and patients or families of patients who experience mental disorders. From the activities that have been carried out, it shows an increase in medication adherence which is marked by the post-test results of 90.56% compared to the pre-test results of 76.26%. These results indicate the achievement of program implementation where the minimum expected post-test value of 80% of participants understand the importance of medication adherence for ODGJ patients. It can be concluded that this community service activity can be carried out as planned and has succeeded in increasing medication adherence for ODGJ patients through a smartphone application-based program.